1975
DOI: 10.1073/pnas.72.4.1263
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP modulates microvillus formation and agglutinability in transformed and normal mouse fibroblasts.

Abstract: We have utilized dark field microscopy to observe the surface microstructure of living cultured cells. Using this method, we have found that dibutyryl cAMP treatment causes regression of the numerous, long cell surface microvilli present on L929 cells. Thirty minutes after removal of dibutyryl cAMP, microvilli reappear. An inhibitor of phosphodiesterase (methylisobutylxanthine) and a stimulator of adenylate cyclase (prostaglandin El), both of which raise cAMP levels, cause regression of microvilli in 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Secondly, mouse type I interferon has recently been shown to influence cyclic nucleotide levels in fibroblast cultures [40], Whether bovine type II interferon or other lymphokines can also influence cyclic nu cleotide levels in cells of lymphoid origin re mains to be elucidated. Thirdly, cyclic nu cleotides were shown to alter tumor cell membranes such that decreased levels of cyclic AMP increased the number of mi crovilli [41], an observation consistent with the notion that better contact could be es tablished between such cells. The suggestion that bovine type II interferon or other lym phokines (macrophage activation factor) had an effect on membranes and their func tion could also be an explanation for the macrophage activation observed.…”
Section: Discussionsupporting
confidence: 49%
“…Secondly, mouse type I interferon has recently been shown to influence cyclic nucleotide levels in fibroblast cultures [40], Whether bovine type II interferon or other lymphokines can also influence cyclic nu cleotide levels in cells of lymphoid origin re mains to be elucidated. Thirdly, cyclic nu cleotides were shown to alter tumor cell membranes such that decreased levels of cyclic AMP increased the number of mi crovilli [41], an observation consistent with the notion that better contact could be es tablished between such cells. The suggestion that bovine type II interferon or other lym phokines (macrophage activation factor) had an effect on membranes and their func tion could also be an explanation for the macrophage activation observed.…”
Section: Discussionsupporting
confidence: 49%
“…For example, depending on cell context, cAMP either stimulates or inhibits cell division. It also causes reversion to a normal phenotype in some transformed cells while being important for differentiation of many cell types (44). These observations may be related to the independent or opposing functions of the two main effectors of cAMP: PKA and EPAC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cAMP has been shown to inhibit lymphocyte mitogenesis have lower cAMP levels during the S and M phases of their growth cycle than during G1 and G2 (35,36). Recent evidence has suggested that cAMP may exert its inhibitory action on cell growth by alterating cell surface properties, possibly through an action on the microtubule system (8,37). Conversely, cGMP has been reported to stimulate growth of both fibroblasts and lymphocytes in culture (11-13, 16, 38) and increases in cellular cGMP content have been implicated in the initiation of proliferation of these cells (7,11,13,16).…”
Section: Methodsmentioning
confidence: 99%